Fast Fourier transform revisited - Pupeikis, Rimantas (Lietuvos matematikos rinkinys, 2015)
Using FFT (fast Fourier transform), it is assumed, that some signal samples in a respective period N are updated by a sensor in real time. It is urgent for every new signal sample to have new frequency samples (f.s.). The idea is that FFT should not be recalculated with every new signal sample, it is needed just to modify it, when the new sample replaces the old one.
Keywords: digital signal processing (DSP); discrete Fourier transform (DFT)